Payas Roko Deeng Buleleng di Desa Liligundi Kecamatan Sukasada Kabupaten Buleleng - Kadek Rendy Wiradana; Ni Made Arshiniwati; suminto (Jurnal IGEL : Journal Of Dance, 2025)
Buleleng has one of the Payas Deeng called Payas Roko Deeng Buleleng precisely in Liligundi Village,Sukasada District. Payas Roko Deeng Buleleng was originally used during the cremation ceremony or palebon by thepuri community precisely during the palebon of I Gusti Putu Gria. This Payas is used as a symbol of final respect fortheir ancestors and those who perform the deeng are relatives or siblings who have died. They must or are required topresent a pair of Deeng, male and female to help guide the deceased's spirit to heaven. Payas Roko Deeng Buleleng iscurrently being studied with the help of a Partner, namely Uje Mua Bali. Uje Mua Bali is located in Buleleng, using theoffline learning method or direct meetings to learn how to install the head shape and clothing of Payas Roko DeengBuleleng. It is hoped that with this Thesis, it can provide broad information about Payas Roko Deeng Buleleng. PayasRoko Deeng has a payasan form that uses a roll of roko roko on the head, uses songket and men use 2-meter longkancut. This has the meaning that roko-roko is used as a symbol of akasa or upper space and kancut as a symbol ofpertiwi (lower space) or land. The unification of these two elements will help the deceased spirit to harmonize the upperand lower realms. A pair of Deeng is also used as a symbol of purusa and pradana or the difference between men andwomen. Payas Roko Deeng Buleleng is also seen based on the current social strata of society, the economy of societycan be seen through the Payas Deeng that is offered.Keywords: Cremation, Payas Roko, Buleleng Deeng